Place matters: A study on the influence of birthplace and the place of development on soccer academy players` careers - Hernández-Simal, L.; Calleja-González, J.; Larruskain, J.; Calvo, A. L.; Aurrekoetxea-Casaus, M. (Sports, 2024)
The effect of birthplace (the place where a player is born and grows up) is one of the key variables associated with soccer player development and achievement. However, recent studies have questioned the influence of contextual variables on selection and promotion processes related to birthplace. The main purposes of this study were: (1) establish whether there is a difference between the birthplace and sporting growth according to the stages of entry into the academy, (2) to evaluate the influence of geographical and contextual variables on sporting development, and (3) assess the chances of making a professional team debut. Applied logistic regression was used in order to analyse the birthplace and growth of 1411 male soccer players, of which 40.1% are incorporated in the U-12 category from a Spanish First division club, and the results showed a statistically significant association between a change from one`s birthplace to the place of sporting growth and later success (79%). Key contextual variables such as number of inhabitants, population density, proximity to sports facilities, average household income and presence of sports clubs have been considered. The analysis of the contextual variables revealed that there was a positive relationship between certain variables, like a higher population, and being selected for the academy (p < 0.01; r = 0.28). Finally, the findings showed that players who experienced a geographical transition were 38% more likely to make a professional debut. The importance of considering the place of sporting growth when analysing the "birthplace effect" has therefore been demonstrated.